Growth and Yield of Wheat as Affected by Boundary Plantation of Populus deltoides M. in Western Uttar Pradesh - Sharma, N. K.; Dadhwal, K. S. (Indian Forester, 2007)
Wheat (Triticum aestivum L.) is one of the most important rabi (winter ) crops being grown with association of boundary plantations of poplar. Growth environment of wheat may be modified and differ from that of pure agricultural system due to shading, competition for nutrients as well as moisture when grown with association of poplar. The aim of this study was to determine the effect of poplar (Populus deltoides M.) boundary plantations on growth and yield of wheat (Triticum aestivum L.) under irrigated condition. The adverse effect of poplar trees on wheat growth increased with advancement in tree age. No significant adverse effect was noticed on wheat grain yield when grown with association of 3 year old boundary plantations of poplar. Whereas, decline of 15.5% was recorded up to a distance of 3 m from the tree base due to 4 year old plantation. Among growth parameters, plant population of wheat suffered heavily up to a distance of 9m. However, relative proportion of effective tillers, dry matter production, 1000 grain weight, straw yield and leaf area index increased significantly between 3-9m distance from tree line, depending upon the age of plantation. Thus, it is inferred that the age of trees was found one of the important factors which influenced both growth and yield of wheat grown adjacent to the tree line.